The Effect of E-Service Quality and E-Trust on Customer Loyalty and Mediating Customer Satisfaction of Internet Banking Users - Herning Indriastuti; Adinda Nur Oktaviani Dwi Putri; Robiansyah Robiansyah; Hairul Anwar (Jurnal Manajemen dan Kewirausahaan, 2022)
These points of research to analyze the effect of e-service quality and e-trust on customer satisfaction and loyalty of internet banking users. The population in this research was Bank of Kaltimtara customers who had used internet banking services. The sampling technique in this study used a non-probability sampling technique with the accidental sampling method with a total sample of 105 respondents. We performed data analysis using PLS (Partial Least Square) software. The results show that: 1) e-service quality has a positive and significant effect on customer satisfaction, 2) e-service quality has an insignificant effect on customer loyalty, 3) e-trust has a positive and significant effect on customer satisfaction, 4) e-trust has an insignificant effect on customer loyalty, 5) customer satisfaction has a positive and significant effect on customer loyalty, 6) e-service quality has a positive and significant effect on customer loyalty through customer satisfaction, and 7) e-trust has a positive and significant effect on customer loyalty through customer satisfaction. The limitations of research on the use of internet banking, comparisons can be made with other regional banks in Indonesia.